High quality draft genome sequence of the slightly halophilic bacterium Halomonas zhanjiangensis type strain JSM 078169T (DSM 21076T) from a sea urchin in southern China. Issue 3 (November 2014) - Zhou, Yu; Li, Rui; Gao, Xiao-Yang; Lapidus, Alla; Han, James; Haynes, Matthew; Lobos, Elizabeth; Huntemann, Marcel; Pati, Amrita; Ivanova, Natalia; Rohde, Manfred; Mavromatis, Konstantinos; et al.
Abstract Halomonas zhanjiangensis Chenet al. 2009 is a member of the genusHalomonas, familyHalomonadaceae, classGammaproteobacteria . Representatives of the genusHalomonas are a group of halophilic bacteria often isolated from salty environments. The type strainH. zhanjiangensis JSM 078169T was isolated from a sea urchin (Hemicentrotus pulcherrimus ) collected from the South China Sea. The genome of strain JSM 078169T is the fourteenth sequenced genome in the genusHalomonas and the fifteenth in the familyHalomonadaceae . The other thirteen genomes from the genusHalomonas areH. halocynthiae, H. venusta, H. alkaliphila, H. lutea, H. anticariensis, H. jeotgali, H. titanicae, H. desiderata, H. smyrnensis, H. salifodinae, H. boliviensis, H. elongata andH stevensii . Here, we describe the features of strain JSM 078169T, together with the complete genome sequence and annotation from a culture of DSM 21076T . The 4, 060, 520 bp long draft genome consists of 17 scaffolds with the 3, 659 protein-coding and 80 RNA genes and is a part ofGenomic Encyclopedia of Type Strains, Phase I: the one thousand microbial genomes (KMG) project.